Comparing topography-based verbal behavior with stimulus selection-based verbal behavior - Sundberg, Carl T. (1990)
Michael (1985) distinguished between two types of verbal behavior: topography-based and stimulus selection-based verbal behavior. The current research was designed to empirically examine these two types of verbal behavior while addressing the frequently debated question, Which augmentative communication system should be used with the nonverbal developmentally disabled person? Four mentally retarded adults served as subjects. Each subject was taught to tact an object by either pointing to its corresponding symbol (selection-based verbal behavior), or making the corresponding sign (topography-based verbal behavior). They were then taught an intraverbal relation, and were tested for the emergence of stimulus equivalence relations. The results showed that signed responses were acquired more readily than pointing responses as measured by the acquisition of tacts and intraverbals, and the formation of equivalence classes. These results support Michael's (1985) analysis, and have important implications for the design of language intervention programs for the developmentally disabled.